Don't be one more logo on the back of the T-shirt: Optimizing sponsorship recall. Issue 2 (2nd April 2016) - Smith, Wayne W.; Pitts, Robert E.; Mack, Rhonda W.; Smith, Jessica T.
ABSTRACT: This article examines participant recall of a total of 87 sponsorships of a local running event over a 5-year period. Participant unaided recall was measured with an online survey administered shortly after the events. The study then used management interviews, event observation, and sponsorship data to provide an in-depth analysis of recall. The results indicate that sponsor engagement with event participants is the key factor in optimizing recall. Sponsors maximizing leveraging opportunities received much higher level of recall than those that did not. Lower level sponsors received almost no unaided recall except in specialized cases.